Can the Indonesian Collective Action Norm of Gotong-Royong Be Strengthened with Economic Incentives? Comparing the Implementation of an Aquaculture Irrigation Policy Program - Adiska Octa Paramita; Stefan Partelow; Achim Schlüter; Nurliah Buhari (International Journal of the Commons, 2023)
The Indonesian multi-level governmental program (PITAP) is a participatory pond irrigation management policy established by the Ministry of Marine Affairs and Fisheries. It aims to catalyze the rehabilitation of irrigation canals to improve water access for small-scale aquaculture farmers. In PITAP, traditional aquaculture farmers are incentivized with government funding to create community-based co-management groups (POKLINA), to maintain the self-governance of their irrigation canals. The logic of PITAP is to encourage POKLINA farmers to rehabilitate their irrigation canals through subsidized labor payments that are coupled with strengthening the strong cultural norm of mutual assistance (i.e., collective action) within Indonesian society called Gotong-Royong. PITAP aims to revitalize Gotong-Royong through subsidized labor compensation with the hope that when the subsidy program is over, Gotong-Royong will be revitalized without external support. In this study, we compare and analyze four villages on Lombok, Indonesia, that participated in PITAP program in 2020 and 2021. The study is supported with empirical data using various qualitative data collection methods, including interviews, participant observations, and the collection of policy documents. We further use the Social-Ecological System Framework (SESF) as a diagnostic tool to structure the data collection process and analysis. Findings indicate that different variables hinder and enable collective action in the four villages, leading to different PITAP program outcomes. The likely reason for this, suggested by our findings, is that each village has different social and ecological conditions that influence intrinsic motivation for collective action. PITAP program either crowds out intrinsic motivation under some conditions or crowds it in under others. This suggests the need to consider contextual adaptations in policy design and implementation to improve outcomes better.